Hak Dan Kewajiban Suami Istri Dalam Rumah Tangga Menurut Hukum Islam Di Sangatta Utara - Nurhikma; Eko Nursalim; Zanuar Anwari (PT. Pustaka Andil Lestari, 2025)
This study aims to analyze the role of the institution in providing legal aid in divorce cases, as well as identifying the challenges faced and solutions that can be applied in providing legal aid in divorce cases in Sangatta. This study uses a qualitative approach with a case study method, involving observation, interviews, and documentation as data collection techniques. Data analysis was carried out using the interactive technique of Miles and Huberman, which includes data collection, data condensation, data presentation, and data verification to produce valid and credible findings. This research was conducted at LBH Suara Rakyat Kutim which is located at Jalan H Abdullah, Gang Pipos, Sangatta Utara Village, Sangatta Utara District, East Kutai and took place from August 2024 to February 2025. The results of the study show that: 1) The Legal Aid Institute (LBH) Suara Rakyat Kutai Timur (SRKT) has a very important role in providing legal aid in divorce cases, especially for the underprivileged. LBH SRKT not only plays a role in providing legal advocacy, assistance in the trial process, and drafting lawsuits, but also in improving public legal literacy through counseling and consultation. 2) LBH SRKT also faces a number of challenges in handling divorce cases, such as limited public legal knowledge, social stigma that prevents individuals from expressing their legal problems, and tensions between state law and customary law that affect the division of joint property and child custody. In facing these challenges, LBH SRKT has implemented various solutions, such as the establishment of Legal Aid Posts (Posbakum) and collaborating with religious courts and district courts to provide legal aid services that are more easily accessible to the public. This solution has proven effective in improving public legal understanding and accelerating the process of resolving divorce cases.